2004
DOI: 10.1063/1.1764491
|View full text |Cite
|
Sign up to set email alerts
|

Protein and solvent dynamics: How strongly are they coupled?

Abstract: Analysis of Raman and neutron scattering spectra of lysozyme demonstrates that the protein dynamics follow the dynamics of the solvents glycerol and trehalose over the entire temperature range measured 100-350 K. The protein's fast conformational fluctuations and low-frequency vibrations and their temperature variations are very sensitive to behavior of the solvents. Our results give insight into previous counterintuitive observations that protein relaxation is stronger in solid trehalose than in liquid glycer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

19
155
0
1

Year Published

2006
2006
2018
2018

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 139 publications
(175 citation statements)
references
References 34 publications
19
155
0
1
Order By: Relevance
“…Indeed, it was previously shown that the ATP hydrolysis of several NBDs, e.g., HisP (33) and Mdl1 (C. van der Does and R. Tampé, unpublished data), is inhibited by glycerol. Moreover, studies on protein and solvent dynamics suggest that compounds such as glycerol can control the solvent dynamics of proteins and affect their activity by forming rigid structures that increase the energy barriers for conformational fluctuations of proteins (34). We also noticed that the E166A mutant is not completely arrested in ATP hydrolysis, but that its activity is decreased 100-fold as compared to that of wt GlcV.…”
Section: Discussionmentioning
confidence: 66%
“…Indeed, it was previously shown that the ATP hydrolysis of several NBDs, e.g., HisP (33) and Mdl1 (C. van der Does and R. Tampé, unpublished data), is inhibited by glycerol. Moreover, studies on protein and solvent dynamics suggest that compounds such as glycerol can control the solvent dynamics of proteins and affect their activity by forming rigid structures that increase the energy barriers for conformational fluctuations of proteins (34). We also noticed that the E166A mutant is not completely arrested in ATP hydrolysis, but that its activity is decreased 100-fold as compared to that of wt GlcV.…”
Section: Discussionmentioning
confidence: 66%
“…In this case, understanding the structure and dynamics of the protein-solvent interface is critical for a comprehensive understanding of the dynamic behavior of proteins. Indeed, it is well known that the dynamics of proteins is slaved to the one of the surrounding solvents [13][14][15][16][17]. In the case of pure trehalose, the dynamic coupling between the protein and the solvent has been studied by Dirama et al [18].…”
Section: Introductionmentioning
confidence: 99%
“…Especially, conformational changes, low-energy vibrational excitations and the corresponding temperature dependences turn out to be very sensitive to the solvents dynamics. [295] We will thus consider the vibrational degrees of freedom of counterions and hydration shells of the solvent as a dynamical bath able to break the electronic phase coherence and additionally to act as a dissipative environment. We do not consider specific features of the environment but represent it in a generic way by a bosonic bath of M harmonic oscillators.…”
Section: 1 the Model Hamiltonianmentioning
confidence: 99%